Menakar Efektivitas PERDA Kabupaten Jember Nomor 5 Tahun 2008 terhadap Perlindungan TKI - Musfianawati Musfianawati; Yuli Winiari Wahyuningtiyas (Fakultas Hukum Universitas Islam Jember, 2017)
Jember is a district with 226 villages and 22 urban villages with the majority of livelihoods being farmers and working in the plantation sector, mostly as laborers, this has caused many economic disparities, in addition to the lack of work opportunities in their own regions and because of the economic pressures that cause many residents choose to work overseas. In addition to the lure of large salaries and easy prerequisites, people choose to work abroad. Most people do not care about whether a person gives a broker or a friend or a government official, the important thing is they can get a job and earn a salary. But the reality is that some of the people who have problems start from not receiving wages, tortured by employers or subject to criminal cases due to various problems in the country people. Seeing the reality, Jember District Government arranged Local Regulation on Service, Placement and Protection of Indonesian Workers of Jember Regency, with the hope that the community can be served from the process before leaving, when they are abroad and after returning to Indonesia. The expectation of a local regulation to protect the community is unlikely to be realized due to the substance of the local regulation giving more role to the private employment placement company (PPTKIS), while the role of the government is limited only to the effort. Extraordinary role is given to the private sector since the start of document management, overseas placement until there is a problem. Including giving a role to the private sector Education and training work and shelter residents who have not yet left abroad. It is prone to arbitrary actions by the private sector. Because the orientation of the company is looking for dependence. The ineffectiveness of local regulations is also supported by the absence of Bupati's regulation as the implementing rule of a Regional Regulation. This means that the existence of Local Regulation No. 5 of 2008 on service, placement and protection of TKI Jember by procedure gives more role of private company so unable to protect the fate of TKI Jember, this Regulation is not Effective because there is no implementation rule so that can not be applied in governance in Kabupaten Jember A ineffective regulation will not be able to solve the problem and can not provide protection in accordance with expectations.